Sustaining Temporal Peace A Worldview for Sustainable Living Inspired by Saint Augustine's Philosophy - Sta. Maria, Joseph Emmanuel D. (2018)
My paper aims to use the philosophical resources of Saint Augustine's thought, particularly as found in the City of God, in order to sketch a basic worldview which can educate and lead people towards living lives that promote sustainable development. Specifically, I wish to show how Saint Augustine's concepts of order, rightly ordered love, and temporal peace can serve as material to create a rough metaphysical framework in which human beings are understood to be an integrated part of a greater whole which is the earth. The ethical corollary of this framework is that human beings should act in such a way that does not damage this greater whole but rather preserves its order and integrity. In doing this, I also hope to show that Saint Augustine's thought can still have relevance for contemporary issues.
Keywords: Augustine, Saint, Bishop of Hippo; Gadotti, Moacir; Sustainable development; Sustainable living; Sustainability; Human beings; Lifestyles